-5(2p+2)-38=3(4p+6)

Simple and best practice solution for -5(2p+2)-38=3(4p+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2p+2)-38=3(4p+6) equation:


Simplifying
-5(2p + 2) + -38 = 3(4p + 6)

Reorder the terms:
-5(2 + 2p) + -38 = 3(4p + 6)
(2 * -5 + 2p * -5) + -38 = 3(4p + 6)
(-10 + -10p) + -38 = 3(4p + 6)

Reorder the terms:
-10 + -38 + -10p = 3(4p + 6)

Combine like terms: -10 + -38 = -48
-48 + -10p = 3(4p + 6)

Reorder the terms:
-48 + -10p = 3(6 + 4p)
-48 + -10p = (6 * 3 + 4p * 3)
-48 + -10p = (18 + 12p)

Solving
-48 + -10p = 18 + 12p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-12p' to each side of the equation.
-48 + -10p + -12p = 18 + 12p + -12p

Combine like terms: -10p + -12p = -22p
-48 + -22p = 18 + 12p + -12p

Combine like terms: 12p + -12p = 0
-48 + -22p = 18 + 0
-48 + -22p = 18

Add '48' to each side of the equation.
-48 + 48 + -22p = 18 + 48

Combine like terms: -48 + 48 = 0
0 + -22p = 18 + 48
-22p = 18 + 48

Combine like terms: 18 + 48 = 66
-22p = 66

Divide each side by '-22'.
p = -3

Simplifying
p = -3

See similar equations:

| -10z+50+2(5x-21)=0 | | f=10(-12)+15 | | 2[3-(5-5x)]-x=10+3(2+3x) | | 9X+3=-12X-42 | | 3-4n+2n=43-78 | | (X^3-x)(3x^2+4)= | | X^2=10x-24 | | 2x^3+3x^2=2x | | (x+4)(x-6)=(2x+3)(x-6) | | (6x+2)(4x+8)= | | 3/12= | | f=-5(-x)-7 | | 5x-3+2x+8= | | f=-5x(-x)-7 | | 5+5[c-4(c-3)]= | | f=-4(-2)+6 | | z^2+7-72=0 | | 1/10(3x-7)=3-10x+5 | | f=-2(-14)+12 | | 8z+5(6+2)+20= | | x^2-36x+72=0 | | 2x-5+3x+15=90 | | 2-7n+2n=3-96 | | 4(c-3)+8=2+c-6 | | f(-14)=-2x+12 | | -28+6k=k-2k | | 16s^2+72s+81=0 | | 6(x+7)= | | -2y^2+8=0 | | 3X-5=-12X+2 | | (2x^2+10)(5-x^2)= | | 4s^2-16=0 |

Equations solver categories